Spiritual Well-Being and Religious Commitment in Explaining Customer Satisfaction and Loyalty in Sharia Banking - Afendi, Arif; Ghofur, Abdul (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2021)
Abstract: This research aims to analyze the impact of spiritual well-being and religious commitment on customer satisfaction. And spiritual well-being, religious commitment, and customer satisfaction to customer loyalty. This research was quantitative with multiple linear regression. The data in this research was primary data with 165 banking customers. The sampling technique was non-probability sampling. The result of the research shows that There was a positive and significant effect of spiritual well-being and religious commitment to customer satisfaction. In addition, customer satisfaction has a positive and significant effect on customer loyalty. Another result shows spiritual well-being and religious commitment have a positive and significant effect on customer loyalty. This study provides information to sharia bank management to pay attention to religious and non-religious factors. For example, social, economic, educational, environmental, cultural factors, the magnitude of profit-sharing, completeness of facilities and infrastructure, and the sophistication of facilities such as ATMs, internet banking, and m-banking are considered in consideration finding customers. These factors contribute very dominantly to determine the level of satisfaction and loyalty of customers.Abstrak: Tujuan dari penelitian ini adalah untuk menguji pengaruh spiritual well-being dan komitmen agama terhadap kepuasan nasabah. Serta pengaruh spiritual well-being, komitmen agama dan kepuasan nasabah terhadap loyalitas nasabah. Jenis penelitian ini adalah kuantitatif dengan regresi linear berganda. Data dalam penelitian ini berupa data primer dengan 165 responden nasabah perbankan. Teknik pengambilan sampel dilakukan dengan menggunakan metode non probability sampling. Hasil penelitian ini menunjukkan bahwa adanya pengaruh positif dan signifikan spiritual well-being dan komitmen agama terhadap kepuasan nasabah. Pengaruh kepuasan nasabah terhadap loyalitas nasabah adalah positif dan signifikan. Selain itu pengaruh spiritual well being dan komitmen agama terhadap loyalitas nasabah adalah positif dan signifikan. Penelitian ini memberikan informasi kepada pihak manajemen bank syariah untuk memperhatikan faktor keagamaan serta non keagamaan, misalnya, faktor sosial, ekonomi, pendidikan, lingkungan, budaya, besarnya bagi hasil, kelengkapan sarana dan prasarana serta kecanggihan fasilitas seperti ATM, internet banking, m-banking sebagai pertimbangan dalam mencari nasabah, karena faktor ini memberikan kontribusi yang sangat dominan untuk menentukan tingkat kepuasan serta loyalitas nasabah.